Bridging the gap between design and engineering in packaging development - ten Klooster, R.; Lutters, D. (Cranfield University Press, 2009)
Packaging designers often come up with splendid design proposals, without being aware of technical, marketing or economical restrictions. This leads to infeasible proposals, so many packaging design projects fail. To bridge the gap between design and marketing, a tool has been developed that shows several designs to an extensive community. Designers now have the possibility to get feedback of the target market on the design proposals. In a case study (redesigning a packaging), the tool clearly showed its advantage. This paper discusses the tool, its usage and its contribution to a more effective and efficient development cycle in packaging development.
Organised by: Cranfield University
Keywords: Packaging; User involvement; Design; Management